Navigating Auditing Risks in the Crypto Asset Landscape - Georgiana-Iulia LAZEA (TRIFA); Ovidiu-Constantin BUNGET; Anca-Diana BALAN; Mircea Stefan SOLOVASTRU (Audit Financiar)
The rise of crypto assets presents unique challenges and risks for auditors, requiring a revaluation of traditional auditing practices. This paper explores the inherent, control, valuation, and related risks associated with crypto assets, emphasising the complexities of valuation, compliance, and fraud detection. Starting from a bibliometric visualisation in VOSviewer, it points out thematic trends and key concepts in crypto auditing. The database was downloaded from the Web of Science Core Collection (2000-2024 Q3). The findings offer valuable insights for auditors, policymakers, investors, researchers, and practitioners who rely on accurate audits to make informed decisions and build trust and transparency in the crypto ecosystem.